Amorphous Fe−Co−P−C Film on a Carbon Fiber Paper Support as an Efficient Electrocatalyst for the Oxygen Evolution Reaction. Issue 15 (13th August 2019) - Lian, Jun; Zhang, Fabao; Lu, ShuQiang; Jiang, Wei; Hu, Qingzhuo; Li, Dongdong; Zhang, Bo
Abstract: Amorphous Fe−Co−P−C films supported on carbon fiber paper were prepared by using an inexpensive conventional magnetron co‐sputtering technique, and the effects of the Co content on electrocatalytic performance were assessed. These Fe 80 - x Co x P13 C7 ( x =20, 40 or 60) films performed well as electrocatalysts and exhibited good durability during the oxygen evolution reaction in 1.0 M KOH. Increases in the Co concentration improved the electrocatalytic activity, and the Fe20 Co60 P13 C7 film produced a low overpotential of approximately 310 mV at 10 mA cm −2, with a low Tafel slope of approximately 31 mV dec −1 . This material also maintained a constant overpotential for at least 20 h. Based on the results of this study, these materials represent a new approach to the development of highly efficient, inexpensive catalysts for water electrolysis. Abstract : Amorphous Fe−Co−P−C films supported on carbon fiber paper were prepared using a facile, inexpensive conventional magnetron co‐sputtering technique without substrate cooling. These Fe80‐ x Co x P13 C7 ( x =20, 40 or 60) films were found to be highly active, robust OER catalysts, and their performance in 1.0 M KOH was improved with increases in Co content during the oxygen evolution reaction.